Hi
(6x-5) (2x-1) = 12x²-6x-10x+5 = 12x²-16x +5
Answer:
C −2a^3+9a^2+45a+6ab^2+18b^2
Step-by-step explanation:
(a+3) ( −2a^2+15a+6b^2)
Distribute the a to the large term in parentheses and the 3 to the large term in parentheses
a ( −2a^2+15a+6b^2)+3 ( −2a^2+15a+6b^2)
−2a^3+15a^2+6ab^2 −6a^2+45a+18b^2
Combine like terms
−2a^3+15a^2−6a^2+6ab^2 +45a+18b^2
-2 a^3 + 9 a^2 + 6 a b^2 + 45 a + 18 b^2
Answer:
C is true also
Step-by-step explanation:
Answer:
6x ≥ -24
x ≥ -4
Step-by-step explanation:
the inequality of Six times a number x is at least −24
6x ≥ -24
Divide each side by 6
6x/6 ≥ -24/6
x ≥ -4